PERAN DAN STRATEGI KOMUNITAS LONTAR DALAM MENYEBARKAN BUDAYA LITERASI DI NUSA TENGGARA BARAT - M. Zaenul Muttaqin; Azhari Evendi; Made Selly Dwi Suryanti (Balitbang Kemendikbud, 2020)
This study aims to analyze the roles and strategies of the Lontar literacy community to introduce literacy culture to the wider community in the West Nusa Tenggara region. Primary data obtained through observation and interviews. Data analysis was carried out systematically by determining the sections and relationships between the data sections. The validity of the data is measured by triangulation and external audit. The results show that the Lontar Community has played its role by providing intensive coaching since 2017 at Taman Baca Masyarakat in two regencies that are tourist destinations, such as TBM Rinjani at the slopes of Rinjani, and the Perpustakaan Adat Bayan for this Traditional Village, North Lombok Regency. In this journey, the Community cooperates with all parties whose mission is to advance education. As for the strategy of spreading literacy culture, the Lontar Community utilizes public space as a place for reading books, scientific discussion and writing in the classroom, and uses social media for literacy campaigns.